Entre poétique documentaire et pédagogie de la preuve. Explorations artistiques et forensiques de l’image 3D avec fleuryfontaine - fleuryfontaine; Cécile Boëx; Milena Jakšić; Stefan Le Courant (Tracés)
The fleuryfontaine duo, Galdric Fleury and Antoine Fontaine, have been exploring 3D tools for the past decade. Educated as architects, their practices engage with contemporary art, counter-investigations of police brutalities and judicial arenas. This interview looks at their career, which moves back and forth between documentary poetics and the pedagogy of proof.